The effect of Moringa oleifera capsule in increasing breastmilk volume in early postpartum patients: A double-blind, randomized controlled trial. - Siraphat Fungtammasan; Vorapong Phupong (PLoS ONE)
Moringa oleifera is an herbal galactagogue that has been used to increase the volume of breastmilk. Few studies have evaluated the effect of Moringa oleifera in breastfeeding. There are conflicting data whether it can increase the volume of breastmilk or not. Thus, the objective of this study is to evaluate the efficacy of Moringa oleifera leaves in increasing the volume of breastmilk in early postpartum mothers. A randomized, double-blind, placebo-controlled trial will be conducted. The outcomes of this study will provide the data of Moringa oleifera as an herbal medication to increase the volume of breastmilk. This information will be used to increase the rate of exclusive breastfeeding for the first 6 months as recommended by the World Health Organization. Clinical trial registration This clinical trial was registered at ClinicalTrials.gov (Clinical trials registration: NCT04487613).